Potensi Bakteri Asam Laktat pada Makanan Fermentasi - Yuni Sine (Fakultas Pertanian, Universitas Timor, 2022)
Lactic acid bacteria have long been used in the food fermentation process, because they have shown a very important role in the fermentation process. LAB group of Gram positive bacteria that can live in various niches. Generally, LAB is used in milk fermentation. In the last few decades, interest in LAB fermentation in vegetable protein sources has begun to be investigated. Lactic acid bacteria themselves can form a consortium with other microorganisms that can improve the quality of fermented food. Many attempts have been made to isolate LAB from legume sources. LAB can utilize carbohydrates from various nuts as prebiotics. This ability makes LAB a good starter for substrate fermentation from various nuts and also as a probiotic.